DETERMINASI PERMINTAAN CPO PADA 5 NEGARA TUJUAN EKSPOR INDONESIA - Eleonora Sofilda (Media Ekonomi, 2021)
This research aims to determine the impact of the Renewable Energy Directive (RED) Policy, Import Duty Rates, and other factors on Indonesian CPO Demand in the five largest export destination countries for Indonesian CPO. Panel data regression with the Random Effect Model (REM) as the relevant model and comparative advantage analysis using RCA were used in this study (Revealed Comparative Advantage). For the period2005-2019, data from the five largest CPO export destination countries for Indonesia were used, including India, China, Netherlands, Italy, and Pakistan. Domestic CPO Production in Indonesia, International CPO Prices, International Soybean Oil Prices, and India's Dummy Import Duty Rates all significantly impact demand for Indonesian Crude Palm Oil, according to the findings. Meanwhile, the rupiah exchange rate against the US dollar and the Dummy Renewable Energy Directive does not affect demand for Crude Palm Oil . Indonesia's crude palm oil (CPO) has a more significant competitive advantage than the rest of the world's CPO producers. The existence of an RCA value more excellent than one indicates that Indonesian CPO commodities have a more significant share of the global CPO commodity export market.